2021
DOI: 10.2174/2589977513666210315095133
|View full text |Cite
|
Sign up to set email alerts
|

Potential of Antibiotics for the Treatment and Management of Parkinson's Disease: An Overview

Abstract: : Evidences have emerged over the last 2 decades to ascertain the proof of concepts viz. mitochondrial dysfunction, inflammation-derived oxidative damage and cytokine-induced toxicity that play a significant role in Parkinson's disease (PD). The available pharmacotherapies for PD are mainly symptomatic and typically indications of L-DOPA to restrain dopamine deficiency and their consequences. In the 21st century, the role of the antibiotics has emerged at the forefront of medicine in health and human illness. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…To conclude, this study revealed that levodopa therapy in PD rat model led to changes in resistance genes, which might be related to alterations in intestinal flora. Antibiotics have emerged as potential drugs to treat PD, but they still face great challenges, such as bacterial resistance ( Yadav et al, 2021 ). Levodopa remains the drug of first choice for PD, although it generates several side effects ( Lane, 2019 ; Cilia et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To conclude, this study revealed that levodopa therapy in PD rat model led to changes in resistance genes, which might be related to alterations in intestinal flora. Antibiotics have emerged as potential drugs to treat PD, but they still face great challenges, such as bacterial resistance ( Yadav et al, 2021 ). Levodopa remains the drug of first choice for PD, although it generates several side effects ( Lane, 2019 ; Cilia et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous experimental and pre-clinical studies have shown that antibiotics may be used as neuroprotective drugs. Additionally, evidence suggests that antibiotics are helpful in reducing neuro-inflammation and mitochondrial dysfunction in addition to avoiding the production of α-synuclein ( Yadav et al, 2021 ). In PD animal models, tetracyclines conferred DA neuroprotection via its anti-inflammatory, anti-oxidant and anti-apoptotic activities, doxycycline can reduce the production of mitochondrial-derived reactive oxygen species and prevent the aggregation and seeding of recombinant α-synuclein, rats exposed to rotenone-induced motor deficits can be improved by minocycline, which increased TH expression and inhibited the release of ROS and NO in the SN ( Sun et al, 2019 ; Dominguez-Meijide et al, 2021 ; Rahmani et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Previous research confirmed the role of Augmentin components (amoxicillin and clavulanic acid) in neurological disorders. In addition, recent research has demonstrated the potential of antibiotic-based therapy for treating and managing Parkinson’s disease and other neurodegenerative disorders ( Yadav et al, 2021 ). In the case of amoxicillin, its administration has been reported to reduce epileptic seizures in patients with epilepsy and to reduce discrete body twitches ( Raposo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although they are mainly used to counteract or prevent bacterial infections, their additional anti-inflammatory, immunomodulator, neuroprotective, antiamyloidogenic and antioxidant properties are becoming of increasing interest in the context of neurological disorders, including neurodegeneration [ 205 , 206 , 207 , 208 , 209 ]. Indeed, beside counteracting dysbiosis and constipation [ 210 ], it has been demonstrated that certain antibiotics can inhibit the activity of matrix metalloproteinases and prevent mitochondria dysfunction, microglia activation, protein misfolding and α-synuclein aggregation [ 211 , 212 , 213 , 214 , 215 ]. For example, treating mice where PD has been induced by MPTP with a cocktail of broad-spectrum antibiotics (ampicillin, metronidazole, and neomycin sulfate) was found to preserve TH and dopamine transporter immunoreactivities, which are generally lost upon MPTP administration [ 216 ].…”
Section: Parkinson’s Disease and Gut Microbiota: Therapeutic Approachesmentioning
confidence: 99%